Evidence to action: Highlights from Transform Nutrition research (2012-2017) - Gillespie, Stuart; Hoddinott, John F.; Nisbett, Nicholas; Arifeen, Shams; van den Bold, Mara (SAGE Publications, 2018)
The Transform Nutrition (Transform) research consortium (2012-2017), led by the International Food Policy Research Institute, sought to generate evidence to inform and inspire action to address undernutrition in 4 high-burden countries (India, Bangladesh, Kenya, and Ethiopia) and globally. Within the context of the literature, this synthesis article brings together core findings of Transform, highlighting priorities for future research.